Comparison of LQR and PSO-based state feedback controller for tracking control of a flexible link manipulaton - Solihin, Mahmud Iwan; Martono, Wahyudi; Legowo, Ari; Akmeliawati, Rini (2010)
In this paper, the state feedback control design problem for tracking control of a flexible link manipulator is considered. The calculation of state feedback control gains is conventionally handled by pole placement method or LQR method via Riccati equation. Unfortunately, they still possess trial and error approach of choosing some parameters. Particularly, choosing elements of Q and R matrices in the state feedback control using LQR method has to be done by trial. Therefore, an intelligent method to resolve this problem is proposed by adopting PSO algorithm. The experimental work is carried out to evaluate the effectiveness of the proposed method.